The Formulation and Characterization of Wound Dressing Releasing S-Nitrosoglutathione from Polyvinyl Alcohol/Borax Reinforced Carboxymethyl Chitosan Self-Healing Hydrogel - Juliana Palungan; Widya Luthfiyah; Apon Zaenal Mustopa; Maritsa Nurfatwa; Latifah Rahman; Risfah Yulianty; Nasrul Wathoni; Jin-Wook Yoo; Nurhasni Hasan (MDPI AG, 2024)
Self-healing hydrogels often lack mechanical properties, limiting their wound-dressing applications. This study introduced S-Nitrosoglutathione (GSNO) to self-healing hydrogel-based wound dressings. Self-healing hydrogel mechanical properties were improved via polymer blends. Applying this hydrogel to the wound site allows it to self-heal and reattach after mechanical damage. This work evaluated polyvinyl alcohol (PVA)-based self-healing hydrogels with borax as a crosslinking agent and carboxymethyl chitosan as a mechanical property enhancer. Three formulations (F1, F4, and F7) developed self-healing hydrogels. These formulations had borax concentrations of 0.8%, 1.2%, and 1.6%. An FTIR study shows that borate ester crosslinking and hydrogen bonding between polymers generate a self-healing hydrogel. F4 has a highly uniform and regular pore structure, as shown by the scanning electron microscope image. F1 exhibited faster self-healing, taking 13.95 ± 1.45 min compared to other formulations. All preparations had pH values close to neutrality, making them suitable wound dressings. Formula F7 has a high drug content (97.34 ± 1.21%). Good mechanical qualities included high tensile stress-strain intensity and Young's modulus. After 28 h of storage at −20 °C, 5 °C, and 25 °C, the self-healing hydrogel's drug content dropped significantly. The Korsmeyer-Peppas release model showed that the release profile of GSNO followed Fickian diffusion. Thus, varying the concentration of crosslinking agent and adding a polymer affects self-healing hydrogels' physicochemical properties.